Comparative analysis of p53 protein expression in early-onset and later-onset colorectal cancers - Rahman, Ashrafur; Shirin, Laila; Sayem, Md Abu; Hasan, Ahmed Sami Al; Alam, M Reazul; Masum, Mahmudul Hasan (Journal of Bangladesh College of Physicians and Surgeons, 2025)
Background: The global incidence of early onset colorectal cancer (CRC) is rapidly rising. However the reason for this and genomic characteristics of early onset CRC is largely unknown. p53 mutation is common in CRC and has been linked to an increased risk of early onset CRC. Methods: All CRC patients operated at Department of Surgical Oncology, NICRH, between October 1, 2021 and September 30, 2022 were included in this study. Demographic and clinical data and surgical findings were recorded. Histopathology and p53 immunohistochemistry (IHC) analysis was done. Patients were categorized in two groups – ‘Early onset’ (diagnosed before 50 years of age) and ‘Late onset’ (diagnosed at or after 50 years of age). p53 protein IHC status (Mutant or Wild type) and other clinicopathological features were compared between the two groups. Result: Out of 129 patients operated, 75 (58.14%) patients were in the early onset group. Compared to the late onset group, early onset patients had longer duration of symptoms (112.4 days vs. 88.7 days; p = .032), more peritoneal seedlings during surgery (14.7% vs. 1.9%, p = .011), and more poor differentiation (p = .062) and higher grades (p = .017) on histopathological analysis. Early onset patients had significantly more p53 mutation on IHC analysis than elderly ones (34.7% vs. 16.7%, p = .018). Age of onset showed no significance on either disease free survival (DFS) or overall survival (OS) in this study. On comparison of patients with either mutant (MT) or wild type (WT) p53 protein, those with MTp53 had more positive family history (20.0% vs. 3.2%, p=.004), higher levels of CEA (6.4 vs. 4.3, p = .028), higher pathological stage (p = .029), more chance of disease progression or recurrence during follow up (p=.035). Short term survival analysis showed patients with p53 mutation had significantly less DFS (p < .001) and OS (p = .001). Conclusion: Early onset CRC was more prevalent in this study, and was associated with significantly more p53 mutation than the elderly patients. The clinical application of p53 mutation analysis by IHC in all CRC cases, particularly in the early onset patients, should be evaluated. J Bangladesh Coll Phys Surg 2025; 43: 5-12